2013
DOI: 10.1093/nar/gks1294
|View full text |Cite
|
Sign up to set email alerts
|

RAG and HMGB1 create a large bend in the 23RSS in the V(D)J recombination synaptic complexes

Abstract: During V(D)J recombination, recombination activating gene proteins RAG1 and RAG2 generate DNA double strand breaks within a paired complex (PC) containing two complementary recombination signal sequences (RSSs), the 12RSS and 23RSS, which differ in the length of the spacer separating heptamer and nonamer elements. Despite the central role of the PC in V(D)J recombination, little is understood about its structure. Here, we use fluorescence resonance energy transfer to investigate the architecture of the 23RSS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 59 publications
(116 reference statements)
15
34
1
Order By: Relevance
“…5B and Fig. S4B), which is consistent with previous studies (6,(24)(25)(26). We also find the K d values for the 12RSS and the 23RSS in the presence of RAG1/2c and HMGB1 are within error of K d values previously reported that were derived from the turnover number (k cat ) (27).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…5B and Fig. S4B), which is consistent with previous studies (6,(24)(25)(26). We also find the K d values for the 12RSS and the 23RSS in the presence of RAG1/2c and HMGB1 are within error of K d values previously reported that were derived from the turnover number (k cat ) (27).…”
Section: Resultssupporting
confidence: 92%
“…This observation is consistent with the HMGB1 dependence of the large bends detected in 12RSS-RAG-HMGB1 or 23RSS-RAG-HMGB1 complexes, although those studies used short oligonucleotide substrates (25,26). We also used this reduction in DNA tether length to determine the K d for the 12RSS and the 23RSS in the presence of RAG1/2c and HMGB1 and found that HMGB1 decreased both similar, consistent with previous observations (6,27).…”
Section: Dynamics Of 12/23 Rule-regulated Bead Release As a Function Ofsupporting
confidence: 90%
“…We also note that the combined bending induced by the RAG-HMGB1 complex within the RSS region is substantial enough to bring nonamer and heptamer regions within FRET range of each other (Fig. S3D), which is in agreement with previous ensemble measurements (19,20).…”
Section: Rag Complex Induces Conformational Changes In 12rss and 23rsssupporting
confidence: 91%
“…Transitions to high FRET for substrates in the presence of Mg 2+ are consistent with RAG1/2-induced bending of both 12RSS and 23RSS substrates previously reported in ensemble (i.e., bulk solution) studies ( Fig. 1 A and B) (19,20). The observed bending induced by RAG1/2 differed from HMGB1 activity in two distinct ways: specificity and stability.…”
Section: Rag Complex Induces Conformational Changes In 12rss and 23rsssupporting
confidence: 90%
See 1 more Smart Citation